Case report: Rare genetic liver disease - a case of congenital hepatic fibrosis in adults with autosomal dominant polycystic kidney disease - Liu, Ying; Zhu, Ping; Tian, Jiajun (Frontiers in Medicine, 2024)
Congenital hepatic fibrosis (CHF) is considered to be a rare autosomal recessive hereditary fibrocystic liver disease, mainly found in children. However, cases of adult CHF with autosomal dominant polycystic kidney disease (ADPKD) caused by PKD1 gene mutation are extremely rare.We report a 31-year-old female patient admitted for esophageal and gastric variceal bleeding.Physical examination revealed significant splenomegaly, biochemical tests showed a slight increase in liver enzymes, and a decrease in platelet count. Imaging examinations showed significant dilatation of the common bile duct and intrahepatic bile ducts, as well as multiple renal cysts. Liver biopsy revealed enlarged portal areas, bridging fibrosis, and numerous variably shaped small bile ducts. Genetic testing identified two unique mutations in the PKD1 gene, identified as biallelic mutations compound heterozygous mutations composed of a mutation inherited from the father (c.8296T>C) and one from the mother (c.9653G>C). Based on multiple test results, the patient was diagnosed with the portal hypertension type CHF associated with ADPKD. During her initial hospital stay, the patient underwent endoscopic treatment for gastrointestinal bleeding. To date, the patient has recovered well. Moreover, a significant reduction in varices was observed in a gastroscopy examination 18 months later.